A new species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) on fig trees in Iran - Moghaddam, Masumeh; Faghih, Hosien (Zootaxa, 2019)
The adult female of a soft scale insect species from Iran, Ericerus farsicus Moghaddam & Faghih, sp. n. (Hemiptera: Coccomorpha: Coccidae), is described and illustrated. The species is placed in the subfamily Eulecaniinae and belongs to the Ericerus-group, based on possession of numerous stigmatic spines in each spiracular cleft. In addition, the soft scale species Saissetia miranda (Cockerell & Parrott) is recorded as new pest on Ficus carica (Moraceae) in Iran.